Prosodic features and prosodic structure : the phonology of suprasegmentals - Fox, Anthony, 1943- (Oxford linguistics., 2000)
This overall view of the nature of prosodic features of language - accent, stress, rhythm, tone, pitch, and intonation - shows how these connect to sound systems and meaning.